Inactivation of sortilin (a novel lysosomal sorting receptor) by dominant negative competition and RNA interference - Lefrancois, Stephane (Biological Procedures Online, 2005)
To assess the role of sortilin in the sorting and trafficking of sphingolipid activator proteins (SAPs) the function of sortilin was abolished by a dominant-negative mutant and by the use of RNAi. Mutant sortilin lacking the carboxyl-terminal region that contains the sorting signal abolished the trafficking of SAPs to the lysosomes. Both sortilin and SAPs were retained in the Golgi apparatus. The use of chemically synthesized siRNA effectively blocked the trafficking of SAPs to the lysosomes as well. Additionally, we created a stable COS-7 cell line transfected with the pSilencer 3.1 H1 neo vector containing a selected siRNA template oligonucleotide (small hairpin interference RNA) where the levels of sortilin were greatly suppressed. The elimination of sortilin by this method will permit to determine whether or not sortilin is involved in a general mechanism of lysosomal sorting that involves the trafficking of various soluble lysosomal proteins other than SAPs.